PENDAMPINGAN PENYUSUNAN LAPORAN HARGA POKOK PESANAN KUSEN CAHAYA INTAN PALEMBANG - Firmansyah; Maria, Maria; Choiruddin; Sukmini Hartati; Emelda Rahmadani Saputri (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2024)
Cahaya Intan Wood and Frame Depot, one of MSMEs in the city of Palembang. This MSME is engaged in woodworking, making frames and tables. As a business that carries out production activities, the Cahaya Intan Wood and Frame Depot requires calculation of the Cost of Production (HPP) which is the basis for determining the selling price. Business owners determine production costs only based on raw materials and labor without taking into account elements of factory overhead costs. For this reason, the team implementing service activities Polsri provides counseling and assistance in preparing HPP reports for MSMEs. With this service activity, business owners will know the costs involved in making accurate frames and ultimately this will lead to the desired selling price and profit. Keywords: Cost of production, orders, frames